2019
DOI: 10.1093/ajcn/nqy385
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomic markers of healthy dietary patterns in US postmenopausal women

Abstract: Background Healthy diet patterns are associated with lower risk of cancer and other chronic diseases. Metabolomics has the potential to expand dietary biomarker development to include dietary patterns, which may provide a complement or alternative to self-reported diet. Objective This study examined the correlation of serum untargeted metabolomic markers with 4 diet pattern scores—the alternate Mediterranean diet score (aMED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…Similar to our investigation, two prior studies comparing hypothesis-driven dietary patterns reported just a modest number of unique dietary pattern and metabolite associations [49,50]. A higher degree of similarities across metabolomic signatures of healthy dietary patterns might indicate a generalized metabolic response of an overall healthy dietary pattern.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to our investigation, two prior studies comparing hypothesis-driven dietary patterns reported just a modest number of unique dietary pattern and metabolite associations [49,50]. A higher degree of similarities across metabolomic signatures of healthy dietary patterns might indicate a generalized metabolic response of an overall healthy dietary pattern.…”
Section: Discussionsupporting
confidence: 86%
“…A higher degree of similarities across metabolomic signatures of healthy dietary patterns might indicate a generalized metabolic response of an overall healthy dietary pattern. Prior studies have reported that a large proportion of the metabolites associated with dietary patterns are lipids [49][50][51]. Lipids represented 63% of the metabolites associated with all three dietary patterns.…”
Section: Discussionmentioning
confidence: 95%
“…It holds a great promise in nutritional epidemiology as an increasing number of food biomarkers have been identified and could be used to facilitate diet assessment in future research [ 1 ]. Several large metabolomics analyses conducted in cohort studies with biospecimens have identified biomarkers of habitual food intakes [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] or dietary patterns [ 15 , 16 ]. In our previous metabolomics analysis of 91 food groups and 1186 serum metabolites among 1369 nonsmoking postmenopausal women in the Cancer Prevention Study II (CPS-II) Nutrition Cohort, we identified 379 diet–metabolite associations with 199 metabolites as putative food biomarkers of 42 food groups/items (one metabolite could be biomarker of multiple food groups/items) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-omics technologies that include genomics, transcriptomics, proteomics, and metabolomics are leading us toward a new approach for nutrition research [22]. In particular, metabolomics reflects the most current biological status of an individual by comprehensively analyzing and quantifying metabolites in samples, such as biofluids and feces [23,24]. This information could help clarify the molecular mechanisms of the effects of diet on health and disease as the closest link to phenotype [25,26].…”
Section: Introductionmentioning
confidence: 99%